PYROSEQUENCING: ITS POTENTIAL AND LIMITATIONS IN DIAGNOSIS OF INHERITED DISEASES IN CATTLE - Н. A. Kirsanova; A. V. Sukhoedova; M. A. Pleskacheva; I. V. Soltynskaya; I. A. Timofeeva; О. V. Prasolova; E. V. Krylova (Ветеринария сегодня)
A large number of diff erent groups of livestock diseases in which heredity plays a signifi cant role are currently reported. In particular, more than 500 genetically determined morphological and functional disorders have been detected in cattle; for 150 of them, specifi c mutations are known. The sale of bovine genetic materials is associated with the spread of various diseases caused by mutations that occur in the prominent representatives of breeds. The abundance of lethal mutations in the populations requires a broader application of molecular diagnostic methods for detection of monogenic hereditary diseases. DNA pyrosequencing, being the most convenient technique for the rapid diagnosis of single nucleotide mutations in the bovine genome that are located in the regions with known nucleotide sequence, has a potential for meeting this need. Pyrosequencing-based methods for identifi cation of the most common signifi cant mutations in Holstein, Simmental, Brown Swiss and Aberdeen Angus cattle were developed, validated and approved at the FGBU “VGNKI”. Such mutations are associated with leukocyte adhesion defi ciency, complex vertebral malformation, uridine monophosphate synthetase defi ciency, citrullinemia, spinal muscular atrophy, spinal cord demyelination, Brown Swiss haplotype 2, Weaver syndrome, developmental duplications, α-mannosidosis, dwarfi sm, bovine male subfertility, trombocytopathya, arachnomelia syndrome, hypozincemia-like syndrome. These methods are intended to test semen in the breeding centres, scientifi c laboratories working in the fi eld of biotechnology and animal reproduction, livestock reproduction centres. The use of the proposed genetic tests to detect mutant alleles, as well as reduced use of mutation-bearing animals in stock breeding will allow minimizing the occurrence of inherited diseases and thus improving the gene pool of cattle in the country.